Mixed powder for 3DP printing and 3DP printing method
By using different particle size metal particles powder, and magnetization and pre -processing, combined with the second magnetization treatment, the problem of poor mass laid quality in 3DP printing has been solved, and higher accumulation density and sintering pieces are achieved. Excellent performance.
Patent Information
- Application Number
- CN202411459841.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, the powder laying quality is poor during the 3DP printing process, and there are many pores on the surface of the powder layer, which is prone to rearrangement of powder particles, resulting in disordered and irregularly distributed pore spaces, resulting in serious printing defects.
Adopt a grade powder, consisting of metal particles of different particle size, including large particle powder, medium granular powder and small particle powder. During the printing process, the second magnetization treatment is performed to improve the effect of powder.
Effectively improve the mass of the powder of the powder of 3DP, reduce the pores and roughness of the surface of the powder layer, increase the density and hardness of the accumulation density and sintering pieces, and avoid the occurrence of printing defects.
Smart Images

Figure CN119346857A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal 3D printing, and in particular to a mixed powder for 3DP printing and a 3DP printing method. Background Art
[0002] Binder jet printing technology, also known as 3DP technology (Three dimensional printing), is an additive manufacturing technology developed by MIT in the early 1990s. 3DP technology is to selectively spray binder on the powder bed according to the sliced contour of the three-dimensional model, so that the binder penetrates into the powder layer by layer to form a green part, and then prepare the final target part after curing, powder removal, degreasing, and sintering. The model processing software of the 3DP printer slices the given three-dimensional model file into a two-dimensional contour file corresponding to the set layer thickness value, which is used as the command input of the printer. During the 3D printing process, the powder hopper spreads a thin layer of powder on the powder bed, and the binder nozzle sprays the binder at the corresponding position of the powder bed according to the instruction information of the two-dimensional contour file, and then the binder in this area is pre-cured by the drying lamp to construct the first layer of the printed entity. When the first layer of printing is completed, the printer system controls the powder bed bottom plate to descend according to the layer thickness setting value, and the powder hopper spreads a new layer of powder on the powder bed, repeating the same binder spraying and pre-curing work until the green part printing is completed. In the 3DP powder spreading process, powder shape and particle size are the main factors affecting the powder spreading quality. At present, spherical powder with coarse particle size (greater than 10μm) is an ideal raw material for 3DP powder spreading. When using spherical powder with coarse particle size (greater than 10μm) for powder spreading, the powder spreading effect is better due to the good powder fluidity, but it is also easy to form a large pore space between the coarse particles, which affects the sintering performance and leads to a significant decrease in the density of the final sintered parts. The use of spherical powder with finer particle size (less than 10μm) is conducive to improving the sintering performance and final density of the powder, but the fluidity of fine powder is poor and the powder spreading effect is poor; at the same time, fine powder is prone to agglomeration at room temperature, and fine powder particles accumulate to form larger irregular morphology particles, which are easy to form larger pores during the powder spreading process, thereby affecting the loose density of the powder in the powder bed, and then affecting the density and mechanical properties of the sintered parts. At the same time, when 3DP printing is in progress, the powder on the powder bed and the binder are in contact with each other. If the powder bed quality is low and there are many pores on the surface of the powder layer, powder particles are prone to rearrangement, resulting in more disordered and irregularly distributed pore spaces between the powder particles, leading to serious printing defects. Summary of the invention
[0003] Based on this, in order to solve the technical problem that the prior art has poor powder spreading quality, many pores on the surface of the powder layer, and powder particles are easily rearranged, so that more disordered and irregularly distributed pore spaces are generated between the powder particles, resulting in serious printing defects, the present invention provides a mixed powder for 3DP printing, and the specific technical solution is as follows:
[0004] A mixed powder for 3DP printing, wherein the graded powder is composed of metal particle powders of different particle sizes, and the different particle sizes are divided into large particle powder, medium particle powder and small particle powder, the particle size of the large particle powder is 50μm to 70μm, the particle size of the medium particle powder is 20μm to 30μm, and the particle size of the small particle powder is 5μm to 10μm; the large particle powder accounts for 45% to 55% of the volume of the mixed powder, the medium particle powder accounts for 25% to 35% of the volume of the mixed powder, and the small particle powder accounts for 10% to 20% of the volume of the mixed powder;
[0005] The small particle powder is subjected to a first magnetization treatment, and then the large particle powder, the medium particle powder and the small particle powder subjected to the first magnetization treatment are mixed for pretreatment.
[0006] Furthermore, small particle powder is added to the emulsion, and the first magnetization treatment time is 20min to 60min under the conditions of magnetic field strength of 2000GS to 3000GS, magnetization speed of 0.5m / s to 1.0m / s, and temperature of 25°C to 40°C. Then, after filtration, washing and drying, small particle powder subjected to the first magnetization treatment is obtained.
[0007] Furthermore, the pretreatment is: adding metal particles to the treatment liquid, heating to 100°C~120°C, treating at a rotation speed of 500r / min~800r / min for 25min~45min, filtering, adding to the treatment liquid again, repeating this process, filtering, placing at 100°C~120°C for drying for 1h~2h, and mixing the powder at 200r / min~250r / min for 1h~5h.
[0008] Furthermore, the treatment liquid is mixed with a silane coupling agent, stearic acid, anhydrous ethanol and water in a volume ratio of (1-5): (1-3): (2-7): (4-15), and placed at a temperature of 45°C to 60°C for 20min to 30min to obtain a treatment liquid.
[0009] Furthermore, the metal particle powder includes at least one of Ni, Mg, Cu, Fe, Al and Ti.
[0010] In addition, the present invention also provides a 3DP printing method, which includes: subjecting the mixed powder to a powder spreading process, a printing process, a thermal curing process, a degreasing process, and a sintering process to obtain a 3DP printed-sintered part.
[0011] Furthermore, the printing process is as follows: the powder thickness is 80 μm to 250 μm, the binder saturation is 50% to 95%, the powder bed temperature is room temperature to 200°C, and during the printing process, a magnetizing component is set in the 3DP printing equipment, and a second magnetizing treatment is performed after spraying the binder, and this is repeated several times.
[0012] Furthermore, the thermal curing process is as follows: the thermal curing temperature is 130° C. to 200° C., and the thermal curing time is 1 hour to 45 hours.
[0013] Furthermore, the degreasing process is as follows: the heating rate is 1.8°C / min to 5°C / min, the degreasing temperature is 300°C to 800°C, the insulation time is 10min to 120min, and protective gas needs to be injected during the degreasing process.
[0014] Furthermore, the sintering process is as follows: the heating rate is 1.8°C / min to 8°C / min, the sintering temperature is ±5°C of the melting point of the large-particle powder material, the insulation time is 10min to 300min, and the sintering process needs to be carried out in a protective gas or vacuum.
[0015] In the above scheme, large-particle powders, medium-particle powders and small-particle powders with different particle size distributions are compounded, and the interaction between particle powders of different sizes, including loosening effect, wall effect and wedging effect, is utilized to reduce the porosity and roughness on the surface of the mixed powder layer, thereby effectively improving the powder spreading quality of the 3DP printing powder, thereby increasing the packing density of the powder and obtaining a better print green density; at the same time, small-particle powders are easy to adhere to the surface of large-particle powders, and rely on the better fluidity of larger-sized particle powders to indirectly drive the flow of small-particle powders, and obtain good flow diffusion on the powder bed, thereby improving the powder spreading effect of small-particle powders. In addition, the first magnetization treatment of small-particle powder can help form a "magnetic resistance" effect, so that small-particle powder can better fill the gap in the mixed powder, thereby increasing the packing density; pre-treatment of large-particle powder, medium-particle powder and magnetized small-particle powder allows grafting groups on the surface of the mixed powder, which not only improves the dispersibility of the mixed powder, but also helps to improve the density and strength of the sintered parts through chemical bonding. Combined with the second magnetization treatment, the density reaches more than 99%, and the Vickers hardness (kg / mm 2) reached 293.4 or above. Overall, the present application optimizes the powder and process to obtain high-quality sintered parts without defects such as expansion, cracking and holes, which can effectively solve the technical problems of poor powder spreading quality in the prior art, more pores on the surface of the mixed powder layer, and easy rearrangement of powder particles, thereby generating more disordered and irregularly distributed pore spaces between the particles, resulting in serious printing defects. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The present invention can be further understood from the following description in conjunction with the accompanying drawings. The components in the figures are not necessarily drawn to scale, but the emphasis is placed on illustrating the principles of the embodiments. In different views, the same reference numerals designate corresponding parts.
[0017] Figure 1 This is a schematic diagram of the structure of a 3DP printing device in Embodiment 1 of the present invention;
[0018] Figure 2 Schematic diagram of the 3DP printing process in Example 1 of the present invention.
[0019] Description of reference numerals:
[0020] 1-scraper; 2-binder supply box; 3-print head; 4-magnetic pole (probe). DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with its embodiments. It should be understood that the specific implementation methods described herein are only used to explain the present invention and do not limit the scope of protection of the present invention.
[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0023] In one embodiment of the present invention, a mixed powder for 3DP printing is provided, wherein the graded powder is composed of metal particle powders of different particle sizes, and the different particle sizes are divided into large particle powder, medium particle powder and small particle powder, the particle size of the large particle powder is 50 μm to 70 μm, the particle size of the medium particle powder is 20 μm to 30 μm, and the particle size of the small particle powder is 5 μm to 10 μm; the large particle powder accounts for 45% to 55% of the volume of the mixed powder, the medium particle powder accounts for 25% to 35% of the volume of the mixed powder, and the small particle powder accounts for 10% to 20% of the volume of the mixed powder;
[0024] The small particle powder is subjected to a first magnetization treatment, and then the large particle powder, the medium particle powder and the small particle powder subjected to the first magnetization treatment are mixed for pretreatment.
[0025] The small-particle powder and medium-particle powder particles in the present invention can fill the pores between the large-particle powder particles. The large-sized particles interact with the small-sized particles to form a wall effect. At the same time, since some of the smaller-sized particles are not completely filled into the large-sized particles, but are sandwiched in the gaps of the large-sized particles, a wedge effect is formed; the interaction between the large-sized powder particles and the small-sized particles will also form a loosening effect. The interaction of the three different-sized powder particles can significantly improve the packing density of the mixed powder and obtain a higher printing green density. Smaller powder particles are easy to adhere to the surface of the large-particle powder, and the better fluidity of the coarse powder is used to indirectly drive the flow of the smaller-particle powder, and obtain good flow diffusion on the powder bed, thereby improving the powder spreading effect of the small-particle powder and reducing the pores and roughness on the surface of the powder layer to improve the powder spreading quality of the 3DP printing powder.
[0026] In one embodiment, the large-particle powder accounts for 50% or 55% of the volume of the mixed powder.
[0027] In one embodiment, the medium-sized powder accounts for 30% or 20% of the volume of the mixed powder.
[0028] In one embodiment, the small particle powder accounts for 20% or 10% of the volume of the mixed powder.
[0029] In one embodiment, the volume ratio of the large-particle powder, the medium-particle powder and the small-particle powder is 50%:30%:20%. Limiting different volume ratios and particle sizes can ensure the powder spreading quality and powder stacking density.
[0030] The volume ratio of the large-particle powder added in the present invention is 60%, the roughness of the powder surface and the pores on the powder layer surface increase, the powder spreading quality decreases, and the packing density of the powder decreases, resulting in a significant decrease in the final sintering density; the volume ratio of the small-particle powder added is 40%, resulting in the small-particle powder being unable to effectively adhere to the surface of the large-particle powder, the small-particle powder has poor fluidity and is prone to agglomeration, which seriously affects the powder spreading quality and cannot play a role in filling the gaps between the large-sized particle powder particles. Therefore, in 3DP printing, large-sized particles dominate the mixed powder under comprehensive consideration of the packing density and powder spreading fluidity. The medium-sized or small-particle powder is a spherical or quasi-spherical powder, or a non-spherical powder. Preferably, the medium-sized and small-particle powders are both spherical or quasi-spherical powders.
[0031] In one embodiment, small particle powder is added to the emulsion, and the first magnetization treatment time is 20min to 60min under the conditions of magnetic field strength of 2000GS to 3000GS, magnetization speed of 0.5m / s to 1.0m / s, and temperature of 25°C to 40°C, and then after filtration, washing and drying, the small particle powder subjected to the first magnetization treatment is obtained.
[0032] In one embodiment, the emulsion is an emulsion used for cooling and lubrication in metal cutting.
[0033] In one embodiment, the pretreatment is: adding metal particles to the treatment liquid, heating to 100°C to 120°C, treating at a speed of 500r / min to 800r / min for 25min to 45min, filtering, adding to the treatment liquid again, repeating this, filtering, placing at 100°C to 120°C for 1h to 2h, and mixing at 200r / min to 250r / min for 1h to 5h. In one embodiment, the treatment liquid is a mixture of silane coupling agent, stearic acid, anhydrous ethanol and water in a volume ratio of (1 to 5): (1 to 3): (2 to 7): (4 to 15), and placing at a temperature of 45°C to 60°C for 20min to 30min to obtain the treatment liquid.
[0034] In one embodiment, the metal particle powder includes at least one of Ni, Mg, Cu, Fe, Al and Ti.
[0035] In one embodiment, the metal particle powder includes at least one of Ni-based powder, Mg-based powder, Cu-based powder, Fe-based powder, Al-based powder and Ti-based powder.
[0036] In one embodiment, the Ni-based powder is Inconel718 (IN718 spherical powder) alloy or Inconel625 alloy.
[0037] In one embodiment, the mass content of Ni in the Inconel 718 alloy is 50% to 55%, the mass content of Cr is 17% to 21%, the mass content of Fe is 15% to 17%, the mass content of Nb is 4.75% to 5.5, and the mass content of Mo is 2.8% to 3.3%.
[0038] In one embodiment, the Fe-based powder includes 022Cr17Ni12Mo2 (also known as 316L stainless steel) and 06Cr19Ni10 (also known as 304 stainless steel powder).
[0039] In one embodiment, the large particle powder is spherical powder.
[0040] In addition, the present invention also provides a 3DP printing method, which includes: subjecting the mixed powder to a powder spreading process, a printing process, a thermal curing process, a degreasing process, and a sintering process to obtain a 3DP printed-sintered part.
[0041] In one of the embodiments, the powder spreading process is as follows: the material falling strength is 60% to 80%, and the scraper speed is 40 mm / min to 80 mm / min.
[0042] In one of the embodiments, the blanking strength may be 60% or 70% or 80%, and the scraper speed may be 40 mm / min or 50 mm / min or 60 mm / min or 70 mm / min or 80 mm / min.
[0043] In one embodiment, the printing process is as follows: the powder thickness is 80 μm to 250 μm, the binder saturation is 50% to 95%, the powder bed temperature is room temperature to 200°C, and during the printing process, a magnetizing component is set in the 3DP printing device, and after spraying the binder, a second magnetization process is performed again, and this is repeated several times. Figure 1 shown.
[0044] In one embodiment, the powder layer thickness is 80μm to 100μm or 100μm to 150μm or 200μm to 250μm; the binder saturation is 50% or 60% or 70% or 80% or 90% or 95%; the powder bed temperature is room temperature 40℃ or 50℃ or 60℃ or 70℃ or 80℃ or 90℃ or 100℃ or 110℃ or 120℃ or 130℃ or 140℃ or 150℃ or 160℃ or 170℃ or 180℃ or 190℃ or 200℃.
[0045] In one of the embodiments, the thermal curing process is as follows: the thermal curing temperature is 130° C. to 200° C., and the thermal curing time is 1 hour to 45 hours.
[0046] In one embodiment, the thermal curing temperature is 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C.
[0047] In one embodiment, the thermal curing time is 6 hours to 10 hours.
[0048] In one embodiment, the degreasing process is as follows: the heating rate is 1.8°C / min to 5°C / min, the degreasing temperature is 300°C to 800°C, the insulation time is 10min to 120min, and protective gas needs to be injected during the degreasing process.
[0049] In one embodiment, the degreasing temperature is 400-600° C., and the holding time is 60 min-120 min.
[0050] In one embodiment, the sintering process is: the heating rate is 1.8℃ / min~8℃ / min, the sintering temperature is the melting point of the large-particle powder material ±5℃, the insulation time is 10min~300min, and the sintering process needs to be carried out in protective gas or vacuum.
[0051] In one embodiment, the protective gas is argon, hydrogen or nitrogen, with a pressure of 0.1 MPa to 40.2 MPa and a flow rate of 0.5 L / min to 1 L / min.
[0052] In one embodiment, the binder is a polymer solution binder.
[0053] In one embodiment, the binder is a water-soluble polymer binder, including water-soluble binders such as polyvinyl alcohol, polyvinyl amine, and starch.
[0054] In one embodiment, the binder further comprises magnetizable nano-metal particles.
[0055] In one embodiment, the magnetizable nano-metal particles are at least one of Fe and Ni. By providing a second magnetization process during the printing process and interacting with the added magnetizable nano-metal particles, the magnetizable nano-metal particles gather in the gaps of the powder layer to fill the gaps and improve the density.
[0056] The above scheme can increase the mass of the powder, and the obtained sintered parts are of high quality without defects such as expansion, cracking and holes. It can effectively solve the technical problems of poor powder spreading quality in the prior art, large number of pores on the surface of the powder layer, and easy rearrangement of powder particles, thereby creating more disordered and irregularly distributed pore spaces between the powder particles, leading to serious printing defects.
[0057] The embodiments of the present invention will be described in detail below with reference to specific examples.
[0058] Embodiment 1:
[0059] A 3DP printing method comprises the following steps:
[0060] A small particle powder (IN718) with a particle size of 5 to 10 μm is added to the emulsion, and the first magnetization treatment time is 30 minutes under the conditions of a magnetic field intensity of 2000 GS, a magnetization speed of 0.5 m / s, and a temperature of 30°C. Then, after filtration, washing, and drying, a small particle powder subjected to the first magnetization treatment is obtained. A silane coupling agent, stearic acid, anhydrous ethanol, and water in a volume ratio of 5:1:7:15 are mixed and placed at a temperature of 45°C for 30 minutes to obtain a treatment solution. 50%:30%:20% of large-particle powder (IN718) with a particle size of 50 to 70 μm, medium-particle powder (IN718) with a particle size of 20 to 30 μm, and small-particle powder subjected to the first magnetization treatment are added to the treatment liquid, heated to 100° C., treated at a speed of 500 r / min for 30 min, filtered, and added to the treatment liquid again, and the process is repeated. After filtering, the powder is dried at 100° C. for 1 h, and mixed at 200 r / min for 2 h to obtain a mixed powder.
[0061] The mixed powder is subjected to 3DP printing, during the printing process, the blanking strength is 80%, the scraper speed is 60 mm / min, the powder layer thickness is 100 μm, the polyvinyl alcohol binder saturation is 60% and contains nano-magnetizable metal particles of iron, the powder bed temperature is 45° C., and during the printing process, a magnetizing component is set in the 3DP printing device, and a second magnetization treatment is performed again after spraying the binder, and this is repeated multiple times, and then the green printed part is subjected to heat curing treatment, the heat curing treatment temperature is 180° C., and the heat curing treatment time is 8 hours to obtain a printed part;
[0062] The printed part was degreased, 5MPa argon was injected during the degreasing process, the maximum degreasing temperature was 600℃, and the holding time was 60min to obtain a printed-degreased part;
[0063] The printed and degreased parts were sintered. During the sintering process, 2 MPa argon was injected, the heating rate was 3 °C / min, the maximum sintering temperature was 1285 °C, and the holding time was 60 min to obtain the printed and sintered parts.
[0064] Embodiment 2:
[0065] A 3DP printing method comprises the following steps:
[0066] A small particle powder (IN718) with a particle size of 5 to 10 μm is added to the emulsion, and the first magnetization treatment time is 20 minutes under the conditions of a magnetic field strength of 2000 GS, a magnetization speed of 1.0 m / s, and a temperature of 40°C. Then, after filtration, washing, and drying, a small particle powder subjected to the first magnetization treatment is obtained. A silane coupling agent, stearic acid, anhydrous ethanol, and water in a volume ratio of 5:1:7:15 are mixed and placed at a temperature of 50°C for 25 minutes to obtain a treatment solution. 50%:30%:20% of large-particle powder (IN718) with a particle size of 50 to 70 μm, medium-particle powder (IN718) with a particle size of 20 to 30 μm, and small-particle powder subjected to the first magnetization treatment are added to the treatment liquid, heated to 120° C., treated at a speed of 500 r / min for 30 min, filtered, and added to the treatment liquid again, and the process is repeated. After filtering, the powder is dried at 100° C. for 1 h, and mixed at 200 r / min for 1 h to obtain a mixed powder.
[0067] The graded powder is subjected to 3DP printing, during the printing process, the blanking strength is 80%, the scraper speed is 60 mm / min, the powder layer thickness is 100 μm, the polyvinylamine binder saturation is 60% and contains nano-magnetizable metal particles of iron, the powder bed temperature is 45° C., and during the printing process, a magnetizing component is set in the 3DP printing device, and a second magnetization treatment is performed again after the binder is sprayed, and this is repeated multiple times, and then the green printed part is subjected to heat curing treatment, the heat curing temperature is 180° C., and the heat curing time is 8 hours, to obtain a printed part;
[0068] The printed part was degreased, 5MPa argon was injected during the degreasing process, the maximum degreasing temperature was 600°C, and the holding time was 60min to obtain a printed-degreased part;
[0069] The printed and degreased parts were sintered, and 2 MPa argon was injected during the sintering process. The heating rate was 5°C / min, the maximum sintering temperature was 1285°C, and the holding time was 60 minutes to obtain the printed and sintered parts.
[0070] Comparative Example 1:
[0071] Compared with Example 2, the volume ratio of the mixed powder in Comparative Example 1 is different. In Comparative Example 1, large-particle powder (IN718) with a particle size of 50-70 μm and small-particle powder (IN718) with a particle size of 5-10 μm are mixed in a volume ratio of 90%:10%, that is, medium-particle powder (IN718) with a particle size of 20-30 μm is not added, and the rest is the same as Example 2.
[0072] Comparative Example 2:
[0073] The difference between Comparative Example 2 and Example 2 is that in Comparative Example 2, only large-particle powder (IN718) with a particle size of 50 to 70 μm is subjected to the printing process, and the rest is the same as Example 2.
[0074] Embodiment 3:
[0075] A 3DP printing method comprises the following steps:
[0076] The small particle powder (316L stainless steel spherical powder) with a particle size of 5 to 10 μm is added to the emulsion, and the first magnetization treatment time is 20 minutes under the conditions of a magnetic field strength of 2000GS, a magnetization speed of 1.0 m / s, and a temperature of 40°C. Then, after filtration, washing and drying, the small particle powder subjected to the first magnetization treatment is obtained; the silane coupling agent, stearic acid, anhydrous ethanol and water with a volume ratio of 5:1:7:15 are mixed, and the mixture is placed at a temperature of 50°C for 25 minutes to obtain a treatment solution, and then the volume ratio of 50% is added to the emulsion. :30%:20% of large-particle powder (316L stainless steel spherical powder) with a particle size of 50 to 70 μm, medium-particle powder (316L stainless steel spherical powder) with a particle size of 20 to 30 μm, and small-particle powder subjected to the first magnetization treatment are added to the treatment liquid, heated to 120° C., treated at a speed of 500 r / min for 30 min, filtered, and added to the treatment liquid again, and the process is repeated. After filtering, the powder is dried at 100° C. for 1 h, and mixed at 200 r / min for 1 h to obtain a mixed powder;
[0077] The graded powder is subjected to 3DP printing, during the printing process, the blanking strength is 80%, the scraper speed is 60 mm / min, the powder layer thickness is 100 μm, the polyvinylamine binder saturation is 60% and contains nano-magnetizable metal particles of iron, the powder bed temperature is 45° C., and during the printing process, a magnetizing component is set in the 3DP printing device, and a second magnetization treatment is performed again after the binder is sprayed, and this is repeated multiple times, and then the green printed part is subjected to heat curing treatment, the heat curing temperature is 180° C., and the heat curing time is 8 hours, to obtain a printed part;
[0078] The printed part was degreased, 5MPa argon was injected during the degreasing process, the degreasing temperature was 600°C, and the holding time was 60min to obtain a printed-degreased part;
[0079] The printed and degreased parts were sintered, and 2 MPa argon was injected during the sintering process. The heating rate was 6°C / min, the maximum sintering temperature was 1370°C, and the holding time was 60 minutes to obtain the printed and sintered parts.
[0080] Embodiment 4:
[0081] A 3DP printing method comprises the following steps:
[0082] The small particle powder (316L stainless steel spherical powder) with a particle size of 5 to 10 μm is added to the emulsion, and the first magnetization treatment time is 20 minutes under the conditions of a magnetic field strength of 2000 GS, a magnetization speed of 1.0 m / s, and a temperature of 40°C. Then, after filtration, washing and drying, the small particle powder subjected to the first magnetization treatment is obtained; the silane coupling agent, stearic acid, anhydrous ethanol and water with a volume ratio of 5:1:7:15 are mixed, and the mixture is placed at a temperature of 50°C for 25 minutes to obtain a treatment solution, and then the volume ratio of 55% is added to the emulsion. :35%:10% of large-particle powder (316L stainless steel spherical powder) with a particle size of 50 to 70 μm, medium-particle powder (316L stainless steel spherical powder) with a particle size of 20 to 30 μm, and small-particle powder subjected to the first magnetization treatment are added to the treatment liquid, heated to 120°C, treated at a speed of 500 r / min for 30 min, filtered, and added to the treatment liquid again, and the process is repeated. After filtering, the powder is dried at 100°C for 1 h, and mixed at 200 r / min for 1 h to obtain a mixed powder;
[0083] The graded powder is subjected to 3DP printing, during the printing process, the blanking strength is 80%, the scraper speed is 60 mm / min, the powder layer thickness is 100 μm, the polyvinylamine binder saturation is 60% and contains nano-magnetizable metal particles of iron, the powder bed temperature is 45° C., and during the printing process, a magnetizing component is set in the 3DP printing device, and a second magnetization treatment is performed again after the binder is sprayed, and this is repeated multiple times, and then the green printed part is subjected to heat curing treatment, the heat curing temperature is 180° C., and the heat curing time is 8 hours, to obtain a printed part;
[0084] The printed part was degreased, 5MPa argon was injected during the degreasing process, the degreasing temperature was 600°C, and the holding time was 60min to obtain a printed-degreased part;
[0085] The printed and degreased parts were sintered, and 2 MPa argon was injected during the sintering process. The heating rate was 6°C / min, the maximum sintering temperature was 1370°C, and the holding time was 60 minutes to obtain the printed and sintered parts.
[0086] Comparative Example 3:
[0087] Compared with Example 4, the difference of Comparative Example 3 is that the ratio of the mixed powder is different. In Comparative Example 3, large-particle powder (316L stainless steel spherical powder) with a particle size of 50 to 70 μm and small-particle powder (316L stainless steel spherical powder) with a particle size of 5 to 10 μm are mixed in a volume ratio of 90%:10%, that is, medium-particle powder (316L stainless steel spherical powder) with a particle size of 20 to 30 μm is not added, and the rest is the same as Example 4.
[0088] Comparative Example 4:
[0089] The difference between Comparative Example 4 and Example 4 is that in Comparative Example 4, only 316L stainless steel spherical pure coarse powder with a particle size of 50-70 μm is used for printing process, and the rest is the same as Example 4.
[0090] Embodiment 5:
[0091] A 3DP printing method comprises the following steps:
[0092] Small particle powder (AlSi10Mg alloy spherical powder) with a particle size of 5 to 10 μm is added to the emulsion, and the first magnetization treatment time is 20 minutes under the conditions of magnetic field intensity of 2000GS, magnetization speed of 1.0 m / s and temperature of 40°C, and then after filtration, washing and drying, the small particle powder subjected to the first magnetization treatment is obtained; silane coupling agent, stearic acid, anhydrous ethanol and water with a volume ratio of 5:1:7:15 are mixed, and placed at a temperature of 50°C for 25 minutes to obtain a treatment solution, and then a volume ratio of 50%: 30%:20% of large-particle powder (AlSi10Mg alloy spherical powder) with a particle size of 50 to 70 μm, medium-particle powder (AlSi10Mg alloy spherical powder) with a particle size of 20 to 30 μm, and small-particle powder subjected to the first magnetization treatment are added to the treatment liquid, heated to 120° C., treated at a speed of 500 r / min for 30 min, filtered, and added to the treatment liquid again, and the process is repeated. After filtering, the powder is dried at 100° C. for 1 h, and mixed at 200 r / min for 1 h to obtain a mixed powder.
[0093] The graded powder is subjected to 3DP printing, during the printing process, the blanking strength is 80%, the scraper speed is 60 mm / min, the powder layer thickness is 100 μm, the polyvinylamine binder saturation is 60% and contains nano-magnetizable metal particles of iron, the powder bed temperature is 45° C., and during the printing process, a magnetizing component is set in the 3DP printing device, and a second magnetization treatment is performed again after the binder is sprayed, and this is repeated multiple times, and then the green printed part is subjected to heat curing treatment, the heat curing temperature is 180° C., and the heat curing time is 8 hours, to obtain a printed part;
[0094] The printed part was degreased, 5MPa argon was injected during the degreasing process, the degreasing temperature was 600°C, and the holding time was 60min to obtain a printed-degreased part;
[0095] The printed and degreased parts were sintered, and 2 MPa argon was injected during the sintering process. The heating rate was 6°C / min, the maximum sintering temperature was 520°C, and the holding time was 60 min to obtain the printed and sintered parts.
[0096] Embodiment 6:
[0097] A 3DP printing method comprises the following steps:
[0098] Small particle powder (AlSi10Mg alloy spherical powder) with a particle size of 5 to 10 μm is added to the emulsion, and the first magnetization treatment time is 20 minutes under the conditions of magnetic field intensity of 2000GS, magnetization speed of 1.0 m / s and temperature of 40°C, and then after filtration, washing and drying, the small particle powder subjected to the first magnetization treatment is obtained; silane coupling agent, stearic acid, anhydrous ethanol and water with a volume ratio of 5:1:7:15 are mixed, and placed at a temperature of 50°C for 25 minutes to obtain a treatment solution, and then a volume ratio of 55%: 35%:10% of large-particle powder (AlSi10Mg alloy spherical powder) with a particle size of 50 to 70 μm, medium-particle powder (AlSi10Mg alloy spherical powder) with a particle size of 20 to 30 μm, and small-particle powder subjected to the first magnetization treatment are added to the treatment liquid, heated to 120°C, treated at a speed of 500 r / min for 30 min, filtered, and added to the treatment liquid again, and the process is repeated. After filtering, the powder is dried at 100°C for 1 h, and mixed at 200 r / min for 1 h to obtain a mixed powder.
[0099] The graded powder is subjected to 3DP printing, during the printing process, the blanking strength is 80%, the scraper speed is 60 mm / min, the powder layer thickness is 100 μm, the polyvinylamine binder saturation is 60% and contains nano-magnetizable metal particles of iron, the powder bed temperature is 45° C., and during the printing process, a magnetizing component is set in the 3DP printing device, and a second magnetization treatment is performed again after the binder is sprayed, and this is repeated multiple times, and then the green printed part is subjected to heat curing treatment, the heat curing temperature is 180° C., and the heat curing time is 8 hours, to obtain a printed part;
[0100] The printed part was degreased, 5MPa argon was injected during the degreasing process, the degreasing temperature was 600°C, and the holding time was 60min to obtain a printed-degreased part;
[0101] The printed and degreased parts were sintered, and 2 MPa argon was injected during the sintering process. The heating rate was 6°C / min, the maximum sintering temperature was 520°C, and the holding time was 60 min to obtain the printed and sintered parts.
[0102] Comparative Example 5:
[0103] Compared with Example 6, the difference of Example 5 is that the ratio of the mixed powder is different. In Example 5, large-particle powder (AlSi10Mg alloy spherical powder) with a particle size of 50-70μm and small-particle powder (AlSi10Mg alloy spherical powder) with a particle size of 5-10μm are mixed in a volume ratio of 90%:10%, that is, medium-particle powder (AlSi10Mg alloy spherical powder) with a particle size of 20-30μm is not added, and the rest is the same as Example 6.
[0104] Comparative Example 6:
[0105] Compared with Example 6, in Comparative Example 6, only the spherical pure coarse powder of AlSi10Mg alloy with a particle size of 50-70 μm is subjected to the printing process, and the rest is the same as Example 6.
[0106] Embodiment 7:
[0107] A 3DP printing method comprises the following steps:
[0108] Small particle powder (Ti6Al4V alloy spherical powder) with a particle size of 5 to 10 μm is added to the emulsion, and the first magnetization treatment time is 20 minutes under the conditions of magnetic field intensity of 2000GS, magnetization speed of 1.0 m / s and temperature of 40°C, and then after filtration, washing and drying, the small particle powder subjected to the first magnetization treatment is obtained; silane coupling agent, stearic acid, anhydrous ethanol and water with a volume ratio of 5:1:7:15 are mixed, and placed at a temperature of 50°C for 25 minutes to obtain a treatment solution, and then a volume ratio of 50%: 30%:20% of large-particle powder (Ti6Al4V alloy spherical powder) with a particle size of 50 to 70 μm, medium-particle powder (Ti6Al4V alloy spherical powder) with a particle size of 20 to 30 μm, and small-particle powder subjected to the first magnetization treatment are added to the treatment liquid, heated to 120° C., treated at a speed of 500 r / min for 30 min, filtered, and added to the treatment liquid again, and the process is repeated. After filtering, the powder is dried at 100° C. for 1 h, and mixed at 200 r / min for 1 h to obtain a mixed powder.
[0109] The graded powder is subjected to 3DP printing, during the printing process, the blanking strength is 80%, the scraper speed is 60 mm / min, the powder layer thickness is 100 μm, the polyvinylamine binder saturation is 60% and contains nano-magnetizable metal particles of iron, the powder bed temperature is 45° C., and during the printing process, a magnetizing component is set in the 3DP printing device, and a second magnetization treatment is performed again after the binder is sprayed, and this is repeated multiple times, and then the green printed part is subjected to heat curing treatment, the heat curing temperature is 180° C., and the heat curing time is 8 hours, to obtain a printed part;
[0110] The printed part was degreased, 5MPa argon was injected during the degreasing process, the degreasing temperature was 600°C, and the holding time was 60min to obtain a printed-degreased part;
[0111] The printed and degreased parts were sintered, and 2 MPa argon was injected during the sintering process. The heating rate was 6°C / min, the maximum sintering temperature was 1500°C, and the holding time was 30 minutes to obtain the printed and sintered parts.
[0112] Embodiment 8:
[0113] A 3DP printing method comprises the following steps:
[0114] Small particle powder (Ti6Al4V alloy spherical powder) with a particle size of 5 to 10 μm is added to the emulsion, and the first magnetization treatment time is 20 minutes under the conditions of magnetic field intensity of 2000GS, magnetization speed of 1.0 m / s and temperature of 40°C, and then after filtration, washing and drying, the small particle powder subjected to the first magnetization treatment is obtained; silane coupling agent, stearic acid, anhydrous ethanol and water with a volume ratio of 5:1:7:15 are mixed, and placed at a temperature of 50°C for 25 minutes to obtain a treatment solution, and then a volume ratio of 55%: 35%:10% of large-particle powder (Ti6Al4V alloy spherical powder) with a particle size of 50-70 μm, medium-particle powder (Ti6Al4V alloy spherical powder) with a particle size of 20-30 μm, and small-particle powder subjected to the first magnetization treatment are added to the treatment liquid, heated to 120° C., treated at a speed of 500 r / min for 30 min, filtered, and added to the treatment liquid again, and the process is repeated. After filtering, the powder is dried at 100° C. for 1 h, and mixed at 200 r / min for 1 h to obtain a mixed powder.
[0115] The graded powder is subjected to 3DP printing, during the printing process, the blanking strength is 80%, the scraper speed is 60 mm / min, the powder layer thickness is 100 μm, the polyvinylamine binder saturation is 60% and contains nano-magnetizable metal particles of iron, the powder bed temperature is 45° C., and during the printing process, a magnetizing component is set in the 3DP printing device, and a second magnetization treatment is performed again after the binder is sprayed, and this is repeated multiple times, and then the green printed part is subjected to heat curing treatment, the heat curing temperature is 180° C., and the heat curing time is 8 hours, to obtain a printed part;
[0116] The printed part was degreased, 5MPa argon was injected during the degreasing process, the degreasing temperature was 600°C, and the holding time was 60min to obtain a printed-degreased part;
[0117] The printed and degreased parts were sintered, and 2 MPa argon was injected during the sintering process. The heating rate was 6°C / min, the maximum sintering temperature was 1500°C, and the holding time was 30 minutes to obtain the printed and sintered parts.
[0118] Comparative Example 7:
[0119] Compared with Example 8, the difference of Example 7 lies in the different ratio of the mixed powder. In Example 7, large-particle powder (AlSi10Mg alloy spherical powder) with a particle size of 50-70 μm and small-particle powder (AlSi10Mg alloy spherical powder) with a particle size of 5-10 μm are mixed in a volume ratio of 90%:10%, that is, medium-particle powder (AlSi10Mg alloy spherical powder) with a particle size of 20-30 μm is not added, and the rest is the same as Example 8.
[0120] Comparative Example 8:
[0121] Compared with Example 8, the difference of Comparative Example 8 is that only spherical pure coarse powder of Ti6Al4V alloy with a particle size of 50-70 μm is added for printing process treatment, and the rest is the same as Example 8.
[0122] The samples of Examples 1 to 8 and the comparative samples of Comparative Examples 1 to 8 were subjected to performance characterization tests, and the performance characterization was to test the density and hardness of the sintered parts, and the Vickers hardness method was used in the hardness test. The mixed powder used was tested for bulk density before 3DP printing. The specific test method is as follows:
[0123] Bulk density test method: Place the mixed powder in a drying oven and dry for 3 hours, then use a Hall flow meter to test according to the national standard GB 1479-84.
[0124] Density method: The density of the sintered parts is measured using the Archimedes drainage method. The sintered parts need to be treated in a water bath during the density test. The water bath temperature is 85°C and the water bath time is 2 hours.
[0125] Vickers hardness test method: Use a cutting machine to cut the sample, then use a metallographic grinder to polish the cut section, wipe the polished surface and place it on a Vickers hardness tester, and use the national standard GB / T 4340.1-2009 to test. The characterization test results are shown in Tables 1 to 4 below.
[0126] Table 1: Comparison results of experimental data of Examples 1 to 2 and Comparative Examples 1 to 2
[0127]
[0128]
[0129] Table 2: Comparison results of experimental data of Examples 3 to 4 and Comparative Examples 3 to 4
[0130]
[0131] Table 3: Comparison results of experimental data of Examples 5 to 6 and Comparative Examples 5 to 6
[0132]
[0133] Table 4: Comparison of experimental data of Examples 7 to 8 and Comparative Examples 7 to 8
[0134]
[0135]
[0136] From the data analysis of Tables 1 to 4, it can be seen that the present application optimizes the ratio of different particle sizes. When small-particle alloy spherical powder of 5 to 10 μm, medium-particle alloy spherical powder of 20 to 30 μm and large-particle alloy spherical powder of 50 to 70 μm are used as raw materials, the graded powder with a volume ratio of large-particle powder, medium-particle powder and small-particle powder of 50%:30%:20% has the best powder spreading effect, and its sintering density is better, and the corresponding sintered parts have the best hardness performance; compared with binary grading and pure coarse powder, the bulk density, sintering density and sintered part hardness performance of the ternary graded powder are better, while the bulk density, sintering density and sintered part hardness performance of the pure coarse powder are significantly worse than those of the graded powder.
[0137] In addition, in order to test the effects of the first magnetization treatment and pretreatment on the sintered parts, the following comparative test 1 was also conducted.
[0138] Comparative Example 9:
[0139] The difference between Comparative Example 9 and Example 2 is that the small particle powder (IN718) in Comparative Example 9 has not undergone the first magnetization treatment, and the rest is the same as Example 2.
[0140] Comparative Example 10:
[0141] The difference between Comparative Example 10 and Example 2 is that Comparative Example 10 is not pre-treated, and the rest is the same as Example 2.
[0142] Comparative Example 11:
[0143] The difference between Comparative Example 11 and Example 2 is that in Comparative Example 11: the small particle powder (IN718) with a particle size of 5 to 10 μm is subjected to the first magnetization treatment, the medium particle powder (IN718) with a particle size of 20 to 30 μm is subjected to pretreatment, and the large particle powder (IN718) with a particle size of 50 to 70 μm is not treated, and the rest is the same as Example 2.
[0144] Comparative Example 12:
[0145] The difference between Comparative Example 12 and Example 2 is that in Comparative Example 12: the small particle powder (IN718) with a particle size of 5 to 10 μm is subjected to the first magnetization treatment, the medium particle powder (IN718) with a particle size of 20 to 30 μm is left untreated, and the large particle powder (IN718) with a particle size of 50 to 70 μm is pretreated, and the rest is the same as Example 2.
[0146] The comparative samples obtained in Comparative Examples 9 to 12 were subjected to characterization tests, and the results are shown in Table 5 below.
[0147] Table 5: Characterization test results 1
[0148]
[0149] From the data analysis of Table 5, it can be seen that in this application, by subjecting the small-particle powder to the first magnetization treatment, it is helpful to form a "magnetic resistance" effect, so that the small-particle powder can better fill the gaps in the mixed powder, thereby increasing the packing density; the large-particle powder, the medium-particle powder and the magnetized small-particle powder are pre-treated to graft groups on the surface of the powder, which not only improves the dispersibility of the powder and the chemical bonding effect, but also helps to increase the density of the sintered parts, which overall helps to obtain sintered parts with excellent apparent quality.
[0150] In order to test the effect of the second magnetization treatment on the printed sintered parts, the following comparative test 2 was also conducted, and the results are shown in Table 6.
[0151] Comparative Example 13:
[0152] The difference between Comparative Example 13 and Example 2 is that Comparative Example 13 does not undergo the second magnetization treatment, and the rest is the same as Example 2.
[0153] Comparative Example 14:
[0154] The difference between Comparative Example 14 and Example 2 is that in Comparative Example 14, no magnetizable nano-metal particles are added to the binder, and the rest is the same as Example 2.
[0155] Table 6: Characterization test results 2
[0156] project Bulk density / % Density / % <![CDATA[Vickers hardness / kg / mm 2 > Comparative Example 13 60.35 91.26 245.7 Comparative Example 14 58.99 89.56 241.8
[0157] From the data analysis in Table 6, it can be seen that the present application helps to improve the density of the printed parts by optimizing the process, performing a second magnetization treatment, and adding an appropriate amount of magnetizable nano-metal particles to the binder.
[0158] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0159] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A mixed powder for 3DP printing, characterized in that: The graded powder is composed of metal particle powders of different particle sizes, and the different particle sizes are divided into large particle powder, medium particle powder and small particle powder, the particle size of the large particle powder is 50μm to 70μm, the particle size of the medium particle powder is 20μm to 30μm, and the particle size of the small particle powder is 5μm to 10μm; the large particle powder accounts for 45% to 55% of the volume of the mixed powder, the medium particle powder accounts for 25% to 35% of the volume of the mixed powder, and the small particle powder accounts for 10% to 20% of the volume of the mixed powder; The small particle powder is subjected to a first magnetization treatment, and then the large particle powder, the medium particle powder and the small particle powder subjected to the first magnetization treatment are mixed for pretreatment.
2. The mixed powder according to claim 1, characterized in that: The small particle powder is added to the emulsion, and the first magnetization treatment time is 20min to 60min under the conditions of magnetic field strength of 2000GS to 3000GS, magnetization speed of 0.5m / s to 1.0m / s, and temperature of 25℃ to 40℃. Then, after filtration, washing and drying, the small particle powder subjected to the first magnetization treatment is obtained.
3. The mixed powder according to claim 1, characterized in that: The pretreatment is as follows: adding metal particles to the treatment liquid, heating to 100°C to 120°C, treating at a speed of 500r / min to 800r / min for 25min to 45min, filtering, adding to the treatment liquid again, repeating this process, filtering, drying at 100°C to 120°C for 1h to 2h, and mixing at 200r / min to 250r / min for 1h to 5h.
4. The mixed powder according to claim 3, characterized in that: The treatment liquid is prepared by mixing a silane coupling agent, stearic acid, anhydrous ethanol and water in a volume ratio of (1-5): (1-3): (2-7): (4-15), and placing the mixture at a temperature of 45° C. to 60° C. for 20 min to 30 min to obtain the treatment liquid.
5. The mixed powder according to claim 1, characterized in that: The metal particle powder includes at least one of Ni, Mg, Cu, Fe, Al and Ti.
6. A 3DP printing method, characterized in that: The 3DP printing method uses the mixed powder according to any one of claims 1 to 5, and the 3DP printing method includes: subjecting the mixed powder to a powder spreading process, a printing process, a thermal curing process, a degreasing process, and a sintering process to obtain a 3DP printed-sintered part.
7. The 3DP printing method according to claim 6, characterized in that: The printing process is as follows: the powder thickness is 80 μm to 250 μm, the binder saturation is 50% to 95%, the powder bed temperature is room temperature to 200° C., and during the printing process, a magnetizing component is set in the 3DP printing device, and a second magnetizing treatment is performed after spraying the binder, and this is repeated several times.
8. The 3DP printing method according to claim 6, characterized in that: The thermal curing process is as follows: the thermal curing temperature is 130° C. to 200° C., and the thermal curing time is 1 hour to 45 hours.
9. The 3DP printing method according to claim 6, characterized in that: The degreasing process is as follows: the heating rate is 1.8°C / min to 5°C / min, the degreasing temperature is 300°C to 800°C, the insulation time is 10min to 120min, and protective gas needs to be injected during the degreasing process.
10. The 3DP printing method according to claim 6, characterized in that: The sintering process is as follows: the heating rate is 1.8°C / min to 8°C / min, the sintering temperature is ±5°C of the melting point of the large-particle powder material, the insulation time is 10min to 300min, and the sintering process needs to be carried out in a protective gas or vacuum.